Combined effects of electrophoresis and thermophoresis in Darcy Forchheimer flow of trihybrid nanofluid over a Riga plate: Yamada-Ota and Xue models - Abbas, Munawar; Khan, Nargis; Hashmi, M. S.; Tawfiq, Ferdous M.; Rezapour, Shahram; Bilal, Muhammad; İnç, Mustafa (Elsevier, 2024)
The physical phenomena of Darcy-Forchheimer flow of trihybrid nanofluid over a Riga plate with the influence of electrophoresis and thermophoresis on the particle deposition and non -uniform heat generation in a porous medium is discussed in this article. In a Marangoni convective flow, this study examined the impact of electrophoresis and thermophoresis on the rate at which aerosol particles deposited across a Riga plate. One of the most basic processes for moving tiny particles across a temperature gradient is known as thermophoresis particle deposition, and it is significant to both aero-solution and electrical engineering. Trihybrid nanofluid containing Cobalt iron oxide (COFe 2 O 4 ) , Manganese Zinc iron oxide ( MnZnFe O 4 ) and Molybdenum disulfides ( MOS 2 ) nanoparticles, and based fluid water is used. For the case of trihybrid nanoparticles, the Xue and Yamada-Ota nanofluid models have been expanded. The objective of this envisaged model is to compare the performance of two renowned ternary hybrid nanofluid models namely Xue and Yamada-Ota. The required similarity transformations are used to translate the set of governing equations into a collection of ODEs. The homotopy analysis method (HAM) is used to analytically solve these simplified equations. For the embedded non -dimensional parameters, the graphic exploration of the velocity, concentration and thermal fields is made. The study's primary outcomes are that as the Marangoni convection parameter is increased, the velocity profile is improved and the temperature and concentration distributions are lowered. The concentration profile decreases with increasing electrophoretic parameter, however the opposite behavior is seen with increasing electrophoretic parameter.
Keywords: Trihybrid nanofluid; Yamada-Ota and Xue models; Electrophoresis and thermophoresis particles; deposition; Marangoni convection; Riga plate